PENGARUH CORPORATE SOCIAL RESPONSIBILITY, KONSERVATISME AKUNTANSI, DAN RISIKO SISTEMATIK TERHADAP EARNING RESPONSE COEFFICIENT - Aulia, Prina Putri; Effendi, Joni; Safri, Safri (JURNAL MITRA MANAJEMEN, 2025)
The research aims to understand the influence of Corporate Social Responsibility, Accounting Conservatism, and Systematic Risk on the Earning Response Coeficient. The population in this study is a company registered in the LQ45 for the period 2019-2023, based on the criteria obtained by 18 companies and 90 number of samples and sampling of these using purposive samplings, which were analyzed using Eviews 12. The results of this study are based on a partial test (t-test) that Corporate Social Responsibility has no influence on the Earning Response Coefficient, Accounting Conservatism has an influence upon the Earning Response Coefficients, and Systematic Risk has an impact on Earning Responsibility Cofficients. The results based on the simultaneous test (F-test) show that Corporate Social Responsibility, accounting conservatism, and systematic risk simultaneously affect the earning response coeficient.Â Keywords: Corporate Social Responsibility, Accounting Conservatism, Systematic Risk, Earning Response Coefficient.